Propagators for noncommutative field theories - Gurǎu, Rǎzvan; Rivasseau, Vincent; Vignes-Tourneret, Fabien (Annales Henri Poincaré, 2006)
In this paper we provide exact expressions for propagators of noncommutative Bosonic or Fermionic field theories after adding terms of the Grosse-Wulkenhaar type to the usual free action in order to ensure Langmann-Szabo covariance. We emphasize the new Fermionic case and we give in particular all necessary bounds for the multiscale analysis and renormalization of the noncommutative Gross-Neveu model.